Analisis Efektivitas Iklan YouTube Shampo Head & Shoulders Menggunakan Metode Customer Response Index (CRI) - Pradhita Lesveva (Universitas 17 Agustus 1945 Surabaya, 2026)
This study aims to analyze the effectiveness of YouTube advertising for Head & Shoulders shampoo using the Customer Response Index (CRI) method, which consists of five stages: awareness, comprehend, interest, intentions, and action. This study uses a descriptive quantitative method by distributing questionnaires to 101 respondents in the Grand Indraprasta Housing Complex, Block A, Sidoarjo. The results showed that each stage of CRI had a percentage above 50%, with a final CRI value of 47.5%. This value is included in the